Multidimensional Budgeting as an Effort to Realize Sustainable Village Development - Winola; Haliah; Nirwana (Jurnal Multidisiplin Madani, 2024)
The budget is viewed from various aspects and is not measured only on the achievement of targets. If the budget is adjusted to the unique economic, socio-cultural, and environmental factors of each region, it will be more effective. The term Multidimensional Based Budget will be used from now on to refer to this budget. This study aims to determine the process and effectiveness of multidimensional-based budgeting in achieving sustainable village development. This study uses a qualitative method with a phenomenological approach. The participants in this study were the Village Head, Village Treasurer and Local Communities who were involved in the planning and budgeting process. The results of the study indicate that the Multidimensional Based Budgeting Management is carried out in accordance with the regulations that have been set by government regulations. In carrying out village fund allocation activities, the village government in the Ganra district first held a meeting with the village community to determine a village development plan according to the needs of the community in each village. Multidimensionality in the village government area in the Ganra sub-district has been right on target, the village government in managing village funds has carried out socialization with the community regarding the village fund budget, and the village government in managing village funds has succeeded in managing the village fund budget in accordance with the needs of the community in the village in Ganra sub-district both from the Economic Aspects, Social & Cultural Aspects and Environmental Aspects